Subtypes of Persistent Postural-Perceptual Dizziness - Yagi, Chihiro (Front Neurol, 2021)
Background: Persistent postural-perceptual dizziness (PPPD) is a persistent chronic vestibular syndrome exacerbated by upright posture/walking, active or passive motion, and exposure to moving or complex visual stimuli. PPPD has four precursors: phobic postural vertigo, space-motion discomfort, visual vertigo, and chronic subjective dizziness. These four diseases share clinical features that form the basis of the diagnostic criteria for PPPD. Semiological similarities do not necessarily mean that PPPD is a single entity. However, if PPPD is not a single disorder but just a composite of four precursors, it may be subdivided according to the characteristics of each precursor. Objective: To test whether PPPD is a single disorder, we attempted a subtyping of PPPD. Methods: One-hundred-eight untreated patients with PPPD were enrolled in the study, who filled out the Niigata PPPD Questionnaire (NPQ) that consists of 12 questions on exacerbating factors for PPPD. A factor analysis of the patients' answers to the NPQ and a subsequent cluster analysis of the patients with PPPD using factors revealed by the factor analysis were performed. To validate our cluster classification, cluster differences were assessed using analysis of variance. Multiple comparison analyses were performed on demographical data, precipitating diseases, the Dizziness Handicap Inventory, the Hospital Anxiety and Depression Scale, and several vestibular tests to characterize each cluster. Results: Factor analysis revealed three underlying factors among the exacerbating factors in the NPQ. Exacerbation by visual stimuli (visual factor) accounted for 47.4% of total variance in the questionnaire. Exacerbation by walking/active motion (active-motion factor) and by passive motion/standing (passive-motion/standing factor) accounted for 12.0 and 7.67% of variance, respectively. Cluster analysis revealed three clusters: the visual-dominant subtype (n = 49); the active motion-dominant subtype (n = 20); and the mixed subtype (n = 39). The patients in the active motion-dominant subtype were significantly older than those in the visual-dominant subtype. There were no significant differences among the subtypes in other demographical data or conventional vestibular tests. Conclusions: The most common main exacerbating factor of PPPD was the visual factor. PPPD may be categorized into three subtypes. Conventional vestibular tests failed to point the characteristics of each subtype.